Acute effects of proprioceptive neuromuscular facilitation and static stretching on maximal voluntary contraction and muscle electromyographical activity in indoor soccer players. (6th May 2013) - Reis, Erika da Fonseca Silva; Pereira, Guilherme Borges; de, Nuno Manuel Frade; Tibana, Ramires Alsamir; Silva, Mauro Fernando; Araujo, Marcia; Gomes, Italo; Prestes, Jonato
Summary The aim was to investigate and compare the effects of proprioceptive neuromuscular facilitation (PNF) and static stretching (SS) on maximal voluntary contraction (MVC) and muscle activation in indoor soccer players. Thirty‐three young adult men were divided into two groups: (i) sedentary and (ii) trained. Each group completed three different experimental trials: SS, PNF and no stretching (NS). The MVC of knee extension was evaluated before and immediately after each condition along with electromyography from the vastus lateralis (VL) and rectus femoris (RF) muscles of the dominant leg. PNF or SS techniques induced no decrease on MVC and muscle electromyographical activity in indoor soccer players (P>0·05). The electromyography of the RF and VL was lower after SS only in the sedentary group (P≤0·05). Short‐duration PNF or SS has no effect on isometric MVC and muscle activity in indoor soccer players.